Application of the conception of traumatic stress in research on children with cancer and their parents - Baran, Joanna (Psychoonkologia, 2009)
The goal of this article is to present the psychological issue of cancer as a traumatic event. It makes it possible for survivors of cancer and their relatives to describe psychological and psychopathological effects. This study is based on a survey of the word literature of psycho-oncology from the last 10 years. Rates of post-traumatic stress disorder (PTSD) and post-traumatic stress symptoms (PTSS) in survivors of childhood cancer and their mothers and fathers are presented. Although the number of cases of post-traumatic stress disorder is not higher than the number in the whole population, it is interesting to note the high frequency of appearance of post-traumatic stress symptoms.